Investigation of the effects of inflammatory and metabolic factors on fracture union in head trauma and long bone fractures : Effect of head trauma and long bone fracture on biomediator levels - Sarı , Abdülkadir; Erdal , Berna; Çelikkol , Aliye; Çetin , Mehmet Ümit (Journal of Surgery and Medicine, 2023)
Background/Aim: Fractures are the most common form of trauma in current orthopedic practice. Although studies have shed light on the relationship between the factors affecting the healing process after fracture, this process is still not fully understood. In this study, we aimed to investigate the changes in serum biomediator levels and fracture healing in different trauma patterns, such as head trauma (HT), long bone fracture (LBF), a combination of HT + LBF injury (CI), and in different time points of the healing period. Methods: Forty Wistar rats were included in the study and divided into five groups. Group 1, the donor group, included rats with HT; Group 2 included rats with LBFs who were administered the serum taken from rats in Group 1; Group 3 included the rats with isolated LBFs; and Group 4 the rats with CI. Group 5 comprised the control rats. An experimental closed HT and fracture model was applied to rats. The rats in Groups 2, 3 and 4 were sacrificed on the 10th, 20th, and 30th days. The biomediator levels in the serum taken after sacrification were studied, while closed femoral fracture models were examined radiologically. Results: Statistically significant differences were found among the groups regarding radiological scores on the 10th, 20th, and 30th days. On Day 10, Group 2a had significantly higher scores than Group 3a (P=0.03), and Group 3a had lower scores than Group 4a (P=0.01). On Day 20, Group 2b had significantly higher scores than Group 3b (P=0.004) but lower than Group 4b (P=0.03). On Day 30, Group 2c had significantly higher scores than Group 3c but lower than Group 4c (P=0.001). The mean Ca, TGF beta 1, beta-catenin, IL-10, IL-17A, TNF alpha, CRP, Wnt-16, ALP, GH, PTH, IL-1 beta, IL-6, and IL-22 levels were significantly different among the groups (P<0.05). No significant difference was observed in the biomediator levels among the groups at different time points of the healing period. Conclusion: We concluded that inflammatory cytokines (IL-1 beta, IL-6, IL-17A, IL-17F, IL-23, and TNF alpha) were elevated in the early period in individuals with isolated head trauma and that this effect could be transferred to other individuals by serum transfer. On the other hand, the negative relationship between the IL-10 level, which is a negative modulator in fracture union, and callus thickness was significant. Our study contributes by providing a molecular description of the positive union effect transferred between individuals by serum. We believe our findings will play a significant role in developing new therapeutic agents for fracture healing.